When a sore throat turns into deadly multiple serous cavity effusions: the role of Prevotella oris in rapidly progressing infection—a case report - Fangqi Zhang; Juan-Li Wang; Jian Zhu; Shaokui Si; Hao Guo; Xiang Yue; Wei Wen (Frontiers in Medicine)
Severe infections that develop rapidly from ordinary symptoms not only increase patient misunderstandings but also lead to excessive detection of these symptoms by physicians. This case study describes a 19-year-old male individual who initially presented with a sore throat and subsequently developed multiple serous cavity effusions that lead to septic pulmonary embolism and septic shock. After multiple cultures of the patient’s sputum yielded no identifiable pathogenic bacteria, the metagenomic next-generation sequencing (mNGS) revealed Prevotella oris as the predominant pathogen present in both the patient’s peripheral blood and the pericardial drainage fluid. The subsequent antibiotic treatment, guided by the mNGS results, along with surgical drainage and mediastinal irrigation, effectively controlled and ultimately cured the patient’s condition. This case is unique because it is the first to show that normally colonizing Prevotella can also cause fatal multiorgan infection as an opportunistic pathogen in a previously healthy young person with no immune-related diseases. The aim of this study is to expand clinical awareness of this common symptom and its potentially fatal outcome.